Binder for electrodes comprising poly (vinylidene fluoride) and hydrophilic polymer

By using adhesive compositions derived from vinylidene fluoride and hydrophilic polymers to form an interpenetrating polymer network, the problems of insufficient adhesive bonding and poor slurry stability in lithium-ion batteries are solved, and better electrode bonding and slurry stability are achieved.

CN119836698APending Publication Date: 2025-04-15ARKEMA FRANCE SA

Patent Information

Application Number
CN202380064438.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-09
Filing Date
2023-09-08
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The adhesive in the existing lithium-ion batteries has insufficient adhesiveness and poor slurry stability in active materials with high nickel content or lithium metal phosphate-based active materials.

Method used

An interpenetrating polymer network is formed using an adhesive composition comprising vinylidene fluoride and a hydrophilic polymer to improve adhesion and maintain slurry stability.

Benefits of technology

It significantly improves the adhesiveness of the electrode and the stability of the slurry, and is suitable for active materials with high nickel content or lithium metal phosphate-based active materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005301098820000151
    Figure BDA0005301098820000151
  • Figure BDA0005301098820000181
    Figure BDA0005301098820000181
Patent Text Reader

Abstract

The present invention relates to a binder composition for a positive electrode comprising a polymer P1 containing repeating units derived from vinylidene fluoride and a hydrophilic polymer P2 containing repeating units derived from at least one monomer of formula R1R2C = C (R3) C (O) R (I) wherein R1, R2 and R3 are independently selected from H and C1-C5 alkyl; r is selected from-NHC (CH3) 2CH2C (O) CH3,-NR 'R "or-OR', where R 'and R" are independently selected from H and C1-C18 alkyl optionally substituted by one or more hydroxyl, thiol or amino functional groups or five to six membered heterocycles comprising at least one nitrogen atom in the ring, characterized in that the hydrophilic polymer P2 has a weight average molecular weight greater than 30000 g / mol, advantageously greater than 50000 g / mol, preferably greater than 65000 g / mol, more preferably greater than 80000 g / mol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates generally to the field of electrical energy storage in rechargeable secondary batteries of the Li-ion type. More precisely, the present invention relates to a binder for electrodes comprising a mixture of at least two polymers, at least one of which is a fluoropolymer. Background Art

[0002] Lithium batteries (batteries) (including lithium metal batteries, lithium ion batteries, lithium polymer batteries and lithium ion polymer batteries) are increasingly being used due to higher voltage and higher energy density than conventional batteries (eg, Ni-MH batteries).

[0003] The basic unit cell of a Li-ion battery or lithium battery comprises an anode (when discharging) and a cathode (also when discharging), which are generally made of lithium insertion compounds of the metal oxide type, such as LiMn2O4, LiCoO2 or LiNiO2, with an electrolyte that conducts lithium ions inserted between the anode and the cathode.

[0004] Rechargeable or secondary cells are more advantageous than primary (non-rechargeable) cells because the relevant chemical reactions occurring at the positive and negative electrodes of the cell are reversible. The electrodes of a secondary cell can be regenerated several times by applying an electrical charge. Many advanced electrode systems have been developed to store charge. At the same time, much effort has been put into developing electrolytes that can improve the capabilities of electrochemical cells.

[0005] For their part, the electrodes generally comprise at least one current collector on which is coated in the form of a film a composite material consisting of the so-called active material (because it is electrochemically active towards lithium), a polymer acting as a binder, plus one or more conductive additives (usually carbon black or acetylene black) and optionally a surfactant.

[0006] Binders are counted among the so-called inactive components, since they do not contribute directly to the battery capacity. However, their key role in electrode processing and their considerable influence on the electrochemical properties of the electrodes have been extensively described. The main relevant physical and chemical properties of binders are thermal stability, chemical and electrochemical stability, tensile strength (strong adhesion and cohesion) and flexibility. The main purpose of using binders is to form a stable network of the solid components of the electrode, i.e. the active material and the conductive agent (cohesion). In addition, the binder must ensure close contact of the composite electrode with the current collector (adhesion).

[0007] Polyvinylidene fluoride (PVDF) is used as a binder in lithium-ion batteries due to its excellent electrochemical stability, good bonding ability, and high adhesion to electrode materials and current collectors. In the wet slurry method for preparing electrodes, active materials and binders are dispersed in a liquid solution. The liquid solution is usually based on an organic solvent or water. The dispersion is cast (cast) on the current collector and then dried in a high-temperature oven to produce an electrode. Unfortunately, the excellent properties provided by fluoropolymers such as PVDF also limit their usable applications. For example, it is difficult to combine fluoropolymers to other materials. Therefore, organic solvents and other organic additives are usually used in coating formulations to provide good adhesion (irreversible adhesion) between PVDF-based polymers, porous separators or electrodes, and optionally added powdered particles. Alternatively, fluoropolymer binders may carry functional groups to facilitate the bonding behavior of polymers. For example, U.S. 2020 / 0407543 discloses a polymer adhesive composition comprising two or more different phases, wherein the phases comprise a highly crystalline fluoropolymer phase and an adhesive fluoropolymer phase, wherein the adhesive fluoropolymer has functional groups.

[0008] The art also discloses an adhesive composition comprising a mixture of a vinylidene fluoride polymer and an acrylic polymer. For example, U.S. 2013 / 252077 describes an electrode for a lithium ion battery, which is operated with a non-aqueous electrolyte. The electrode comprises an active material and a binder, and the binder comprises a vinylidene fluoride polymer and an acrylic polymer. EP 2953 193 describes an adhesive for a lithium ion battery, which comprises a fluorine-containing polymer and an acrylic polymer containing a nitrile group. WO 97 / 27260 describes an electrode comprising a collector made of metal, which is coated with a layer comprising an active material and an adhesive. The adhesive comprises at least two of the following three components: a vinylidene fluoride polymer, an acrylic or methacrylic polymer comprising a functional group capable of being fixed to a metal, and a vinylidene fluoride copolymer. EP 3 796430 discloses an electrode mixture comprising an adhesive composition, the adhesive composition comprising a vinylidene fluoride copolymer and an acrylic polymer having a low weight average molecular weight. However, the adhesion of the adhesive composition is still unsatisfactory and can still be improved.

[0009] Therefore, there remains a need to develop new binders and electrode compositions for Li-ion batteries with improved adhesion while maintaining slurry stability, especially for active materials with high nickel content or based on lithium metal phosphates. Summary of the invention

[0010] According to a first aspect, the present invention provides a binder composition for a positive electrode, comprising a polymer P1 and a hydrophilic polymer P2, wherein the polymer P1 comprises repeating units derived from vinylidene fluoride, and the hydrophilic polymer P2 comprises at least one repeating unit derived from at least one compound of formula R 1 R 2 C=C(R 3 )C(O)R(I) monomer M1 repeating unit, wherein R 1 , R 2 and R 3 R is selected from -NHC(CH3)2CH2C(O)CH3, -NR'R" or -OR', wherein R' and R" are independently selected from H and C1-C5 alkyl; 18 Alkyl groups, which are optionally substituted by one or more hydroxyl, thiol or amino functional groups or a five- to six-membered heterocycle containing at least one nitrogen atom in the ring; characterized in that the weight-average molecular weight of the hydrophilic polymer P2 is greater than 30,000 g / mol, advantageously greater than 50,000 g / mol, preferably greater than 65,000 g / mol, more preferably greater than 80,000 g / mol.

[0011] The present invention provides a binder which, when used in an electrode coating formulation, has improved adhesion to electrodes while also maintaining slurry stability. Applicants have unexpectedly discovered that the molecular weight of the hydrophilic polymer (denoted P2 in this application) strongly affects the adhesive properties of the binder.

[0012] According to a preferred embodiment, said polymer P1 and said polymer P2 form an interpenetrating polymer network. The Applicant has unexpectedly observed that the adhesive properties of the adhesive are further improved when an interpenetrating polymer network is present.

[0013] According to a preferred embodiment, the interpenetrating polymer network is formed by at least one 1 R 2 C=C(R 3 )C(O)R(I) by polymerizing the monomer (M1) in the presence of the polymer P1 as a seed.

[0014] According to a preferred embodiment, the polymer P1 is chosen from polyvinylidene fluoride homopolymers and copolymers based on polyvinylidene fluoride comprising at least one comonomer compatible with vinylidene fluoride.

[0015] According to a preferred embodiment, the comonomer is selected from vinyl fluoride, tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, chlorotrifluoroethylene, trifluoropropylene, tetrafluoropropylene, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene, perfluoroalkyl vinyl ether, bromotrifluoroethylene, chlorofluoroethylene, chlorotrifluoroethylene, chlorotrifluoropropylene and ethylene, or a mixture thereof.

[0016] According to one embodiment, the polymer P1 contains monomer units having at least one of the following functional groups: carboxylic acid, carboxylic anhydride, carboxylic ester, epoxy, amide, hydroxyl, carbonyl, mercapto, sulfide, oxazoline, phenol, ester, ether, siloxane, sulfonic acid, sulfuric acid, phosphoric acid or phosphonic acid.

[0017] According to a preferred embodiment, the hydrophilic polymer P2 comprises at least a repeating unit derived from at least one monomer M1 selected from the following: acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-dodecyl acrylate, amyl acrylate, isoamyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, diacetone acrylamide, lauryl acrylate, n-octyl acrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-dodecyl methacrylate, amyl methacrylate, isoamyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, n-octyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl methacrylate and a combination thereof.

[0018] According to a preferred embodiment, the mass ratio P1 / P2 varies from 99 / 1 to 5 / 95.

[0019] According to a preferred embodiment, the polymer P1 has a melt viscosity greater than 100 Pa.s, preferably greater than 500 Pa.s, more preferably greater than 1000 Pa.s, measured according to ASTM D-3835 method at 232°C and 100 sec-1.

[0020] According to a second aspect, the present invention provides a method for producing an adhesive composition, comprising the following steps:

[0021] a) providing an aqueous solution comprising a polymer P1 comprising repeating units derived from vinylidene fluoride;

[0022] b) adding at least one compound of formula R as defined in the present application 1 R 2 C=C(R 3 )C(O)R(I) monomer M1 and optionally one or more monomers from which the repeating units of the hydrophilic polymer P2 are derived;

[0023] c) adding an initiator and initiating the polymerization of the monomer M1 and optionally one or more monomers from which the repeating units of the hydrophilic polymer P2 are derived, to prepare the adhesive composition according to the invention.

[0024] According to a preferred embodiment, step b) is carried out in the absence of chain transfer agents or in the presence of less than 1.2 wt. %, preferably less than 1.0 wt. %, of chain transfer agents, based on the total weight of all monomers added in step b).

[0025] According to a third aspect, the present invention provides an electrode composition comprising the binder composition according to the present invention, a conductive agent and an active material.

[0026] According to a preferred embodiment, the conductive agent includes one or more materials selected from carbon black, carbon nanotubes, carbon fibers or metal powders.

[0027] According to a preferred embodiment, the active material is selected from lithium salts of transition metal oxides, sulfides, phosphates and hydroxides; preferably, the active material is selected from lithium metal phosphates (having a composition represented by LiMPO4, M represents Fe, Mn, Co, or Ni), LiCoO2, LiNi x Co 1-x O2, LiMn2O2, LiNiO2, LiNi x Co y Mn z O m 、LiNi x Co y Al z O m and LiNi x Mn y Al z O m , wherein x+y+z=1, and m is an integer representing the number of oxygen atoms in the oxide to provide electron balance molecules; in particular, the active material is selected from LiFePO4 and LiNi x Co y Mn z O m , wherein x is greater than or equal to 0.6, y is less than or equal to 0.2, z is greater than or equal to 0.2, and x+y+z=1, and m is an integer representing the number of oxygen atoms in the oxide to provide electron balance molecules.

[0028] According to a fourth aspect, the present invention provides a positive electrode comprising a current collector and an electrode composition according to the present invention disposed on at least one surface of the current collector.

[0029] According to a fifth aspect, the present invention provides a Li-ion secondary battery comprising a negative electrode, a positive electrode according to the present invention, and a separator between the negative electrode and the positive electrode.

[0030] According to a sixth aspect, the present invention provides an electrochemical device comprising a negative electrode, a positive electrode according to the present invention and an electrolyte comprising lithium. DETAILED DESCRIPTION

[0031] The present invention is now described in more detail in a non-limiting manner in the following description. According to various embodiments, the adhesive includes the following features in appropriate combination. Unless otherwise stated, the contents shown are expressed by weight. For all indicated ranges, unless otherwise stated, the limits are included.

[0032] According to a first aspect of the present invention, a binder composition for a positive electrode is provided. According to a preferred embodiment, the binder composition comprises a polymer P1 and a hydrophilic polymer P2 as defined in the present application. The material is used as a polymeric binder or binding component on the positive electrode. Unexpectedly, it has been found that a binder composition comprising particles of a fluoropolymer P1 and a hydrophilic polymer P2 provides a better compromise of properties than a known composition consisting of a fluoropolymer.

[0033] The polymer P1 comprises repeating units derived from vinylidene fluoride (CH2=CF2). In a preferred embodiment, the polymer P1 is selected from polyvinylidene fluoride homopolymers and polyvinylidene fluoride-based copolymers comprising at least one comonomer compatible with vinylidene fluoride. The comonomer compatible with vinylidene fluoride may be halogenated (fluorinated, chlorinated or brominated) or non-halogenated.

[0034] The comonomer may be selected from vinyl fluoride, tetrafluoroethylene, hexafluoropropylene, trifluoropropylene, tetrafluoropropylene, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene, perfluoroalkyl vinyl ether, bromotrifluoroethylene, chlorofluoroethylene, chlorotrifluoroethylene, chlorotrifluoropropylene and ethylene, or a mixture thereof.

[0035] Examples of trifluoropropenes are in particular 3,3,3-trifluoropropene. Tetrafluoropropene may be, for example, 2,3,3,3-tetrafluoropropene or 1,3,3,3-tetrafluoropropene. Pentafluoropropene may be, for example, 1,1,3,3,3-pentafluoropropene or 1,2,3,3,3-pentafluoropropene. Perfluoroalkyl vinyl ethers are, for example, those of the general formula Rf-O-CF=CF2, Rf being an alkyl group, preferably a C1 to C4 alkyl group (preferred examples are perfluoropropyl vinyl ether and perfluoromethyl vinyl ether). Chlorofluoroethylene may represent 1-chloro-1-fluoroethylene or 1-chloro-2-fluoroethylene. 1-chloro-1-fluoroethylene isomers are preferred. Chlorotrifluoropropylene is preferably 1-chloro-3,3,3-trifluoropropene or 2-chloro-3,3,3-trifluoropropene.

[0036] The polymer P1 may also comprise non-halogenated monomers such as ethylene and / or acrylic acid or methacrylic acid comonomers.

[0037] The polymer P1 may contain at least 50 mol % of vinylidene fluoride, advantageously at least 60 mol % of vinylidene fluoride, preferably at least 70 mol % of vinylidene fluoride, more preferably at least 80 mol % of vinylidene fluoride and in particular at least 90 mol % of vinylidene fluoride.

[0038] In one embodiment, the polymer P1 may contain monomer units with at least one of the following functional groups: carboxylic acid, carboxylic anhydride, carboxylate, epoxy (e.g. glycidyl), amide, hydroxyl, carbonyl, mercapto, sulfide, oxazoline, phenols, esters, ethers, siloxanes, sulfonic acids, sulfuric acids, phosphoric acids or phosphonic acids. According to techniques well known to those skilled in the art, the functional groups are introduced by chemical reactions, which may be grafting or copolymerization of fluorinated monomers with monomers having at least one of the functional groups and a vinyl functional group capable of copolymerizing with the fluorinated monomers.

[0039] According to one embodiment, the polymer P1 may comprise repeating units carrying a carboxylic acid functional group, which is a (meth)acrylic acid type group selected from acrylic acid, methacrylic acid, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate and hydroxyethylhexyl (meth)acrylate.

[0040] According to one embodiment, the units carrying a carboxylic acid function may additionally contain heteroatoms selected from oxygen, sulfur, nitrogen and phosphorus.

[0041] According to one embodiment, the functionality is introduced by means of a transfer agent used during the synthesis process. The transfer agent is a polymer having a molar mass less than or equal to 20 000 g / mol and carrying functional groups selected from the following groups: carboxylic acids, carboxylic anhydrides, carboxylates, epoxy groups (e.g. glycidyl groups), amides, hydroxyls, carbonyl groups, mercapto groups, sulfides, oxazolines, phenols, esters, ethers, siloxanes, sulfonic acids, sulfuric acids, phosphoric acids or phosphonic acids. An example of a transfer agent of this type is an oligomer of acrylic acid. According to a preferred embodiment, the transfer agent is an oligomer of acrylic acid having a molar mass less than or equal to 20 000 g / mol.

[0042] The content of functional groups of polymer P1 is at least 0.01 mol %, preferably at least 0.1 mol %, and at most 15 mol %, preferably at most 10 mol %.

[0043] In a particular embodiment, the polymer P1 is a homopolymer of vinylidene fluoride or the polymer P1 comprises repeating units derived from vinylidene fluoride and repeating units with a carboxylic acid functional group, wherein the carboxylic acid functional group is a (meth)acrylic acid type group selected from acrylic acid, methacrylic acid, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate and hydroxyethylhexyl (meth)acrylate.

[0044] As used herein, the term "high molecular weight" is understood to mean a polymer P1 having a melt viscosity greater than 100 Pa.s, preferably greater than 500 Pa.s, more preferably greater than 1000 Pa.s, measured according to ASTM D-3835 method at 232°C and 100 sec-1.

[0045] The polymers P1 used in the present invention are obtainable by known polymerization processes, such as emulsion polymerization or suspension polymerization. According to one embodiment, they are prepared by an emulsion polymerization process in the absence of fluorinated surfactants.

[0046] The polymerization of polymer P1 produces a latex having a solid content of typically 10% to 60% by weight, preferably 10% to 50% by weight and having a volume average particle size of less than 1 micron, preferably less than 1000nm, preferably less than 800nm, and more preferably less than 600nm. The volume average size of the particles is typically at least 20nm, preferably at least 50nm, and advantageously the average size is in the range of 100-400nm. The polymer particles can form agglomerates having a volume average size of 1 to 30 microns, and preferably 2 to 10 microns. A Nicomp CW380 particle size analyzer (light scattering) is used to measure the volume average particle size of the latex particles. During formulation and application to the substrate, the agglomerates can be broken into discrete particles.

[0047] According to some embodiments, polymer P1 (homopolymer or copolymer) is composed of bio-based vinylidene fluoride. The term "bio-based" means "derived from biomass". This makes it possible to improve the ecological footprint of the film. Bio-based vinylidene fluoride may be characterized in that the content of renewable carbon (i.e., carbon of natural origin and derived from biomaterial or biomass) is at least 1 atom%, as determined by the content of 14C according to standard NF EN 16640. The term "renewable carbon" means that the carbon is of natural origin and derived from biomaterial (or derived from biomass), as shown below. According to some embodiments, the biocarbon content of VDF may be greater than 5%, preferably greater than 10%, preferably greater than 25%, preferably greater than or equal to 33%, preferably greater than 50%, preferably greater than or equal to 66%, preferably greater than 75%, preferably greater than 90%, preferably greater than 95%, preferably greater than 98%, preferably greater than 99%, advantageously equal to 100%.

[0048] As mentioned above, the adhesive composition comprises a hydrophilic polymer P2. The hydrophilic polymer P2 comprises at least one compound derived from at least one of the formula R 1 R 2 C=C(R 3 )C(O)R(I) monomer M1 repeating unit, wherein R 1 , R 2 and R 3R is selected from -NHC(CH3)2CH2C(O)CH3, -NR'R" or OR', wherein R' and R" are independently selected from H and C1-C5 alkyl, which are optionally substituted by one or more hydroxyl, thiol or amino functional groups or a five- to six-membered heterocyclic ring containing at least one nitrogen atom in the ring. 18 alkyl.

[0049] In a preferred embodiment, the monomer M1 has the formula R 1 R 2 C=C(R 3 )C(O)R(I), where R 1 , R 2 and R 3 R is selected from -NHC(CH3)2CH2C(O)CH3, -NR'R" or OR', wherein R' and R" are independently selected from H and C1-C5 alkyl, optionally substituted by one or more hydroxyl, thiol or amino functional groups or a five- to six-membered heterocyclic ring containing at least a nitrogen atom in the ring; 15 alkyl.

[0050] In a preferred embodiment, the monomer M1 has the formula R 1 R 2 C=C(R 3 )C(O)R(I), where R 1 , R 2 and R 3 R is selected from -NHC(CH3)2CH2C(O)CH3, -NR'R" or OR', wherein R' and R" are independently selected from H and C1-C5 alkyl, optionally substituted by one or more hydroxyl, thiol or amino functional groups or a five- to six-membered heterocyclic ring containing at least a nitrogen atom in the ring; 10 alkyl.

[0051] In a preferred embodiment, the monomer M1 has the formula R 1 R 2 C=C(R 3 )C(O)R(I), where R 1 , R 2 and R 3 independently selected from H and C1-C5 alkyl; R is selected from -OR', wherein R' is selected from H and C1-C5 alkyl optionally substituted with one or more -OH functional groups 10 alkyl.

[0052] In a preferred embodiment, the monomer M1 has the formula R 1 R 2 C=C(R 3 )C(O)R(I), where R 1, R 2 and R 3 independently selected from H and C1-C3 alkyl; R is selected from -OR', wherein R' is selected from H and C1-C3 optionally substituted with one or more -OH functional groups 10 alkyl.

[0053] In a more preferred embodiment, the monomer M1 has the formula R 1 R 2 C=C(R 3 )C(O)R(I), where R 1 , R 2 and R 3 Independently selected from H and C1-C3 alkyl; R is selected from -OR', wherein R' is selected from H and C1-C5 alkyl optionally substituted with one or more -OH functional groups.

[0054] In a preferred embodiment, the hydrophilic polymer P2 comprises at least a repeating unit derived from at least one monomer M1 selected from the group consisting of acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-dodecyl acrylate, amyl acrylate, isoamyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, diacetone acrylamide, lauryl acrylate, n-octyl acrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-dodecyl methacrylate, amyl methacrylate, isoamyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, n-octyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl methacrylate, and combinations thereof. Among them, alkyl acrylates having an alkyl group having 1 to 8 carbon atoms are preferred, and alkyl acrylates having an alkyl group having 1 to 5 carbon atoms are more preferred. These compounds can be used alone or as a mixture of two or more. In a more preferred embodiment, the hydrophilic polymer P2 comprises at least a repeating unit derived from at least one monomer M1, the monomer M1 being selected from acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, amyl acrylate, isoamyl acrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, amyl methacrylate, isoamyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl methacrylate and combinations thereof; in particular, selected from acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, propyl acrylate, ethyl methacrylate, propyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl methacrylate and combinations thereof.

[0055] In a preferred embodiment, the weight average molecular weight Mw of the hydrophilic polymer P2 is greater than 30,000 g / mol, advantageously greater than 40,000 g / mol, preferably greater than 50,000 g / mol, more preferably greater than 65,000 g / mol, in particular greater than 80,000 g / mol, more in particular greater than 100,000 g / mol.

[0056] The hydrophilic polymer P2 may also comprise repeating units derived from a monomer M2 copolymerizable with the monomer M1. The monomer M2 may be:

[0057] - (A) an alkenyl compound containing a functional group, or

[0058] - (B) an alkenyl compound having no functional group; or a mixture thereof.

[0059] The alkenyl compound (A) containing a functional group includes, for example, α, β-unsaturated carboxylic acids such as acrylic acid, methacrylic acid, fumaric acid, crotonic acid, itaconic acid, etc.; vinyl ester compounds such as vinyl acetate, vinyl neodecanoate, etc.; amide compounds such as acrylamide, methacrylamide, N-methylacrylamide, N-methylmethacrylamide, N-hydroxymethylacrylamide, N-hydroxymethylmethacrylamide, N-alkylacrylamide, N-alkylmethacrylamide, N,N-dialkylacrylamide, N,N-dialkylmeth ... Acrylic acid esters such as 2-hydroxyethyl acrylate, N-dialkylaminoethyl acrylate, glycidyl acrylate, n-dodecyl acrylate, fluoroalkyl acrylate, etc.; and methacrylates such as dialkylaminoethyl methacrylate, fluoroalkyl methacrylate, 2-hydroxyethyl methacrylate, n-octyl methacrylate, tert-butyl methacrylate, glycidyl methacrylate, ethylene glycol dimethacrylate, etc.; maleic anhydride, and alkenyl glycidyl ether compounds such as allyl glycidyl ether, etc. Among them, acrylic acid, methacrylic acid, itaconic acid, fumaric acid, N-hydroxymethyl acrylamide, N-hydroxymethyl methacrylamide, diacetone acrylamide, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, and allyl glycidyl ether are preferred. These compounds can be used alone or as a mixture of two or more.

[0060] The alkenyl compound (B) not containing a functional group includes, for example, conjugated dienes such as 1,3-butadiene, isoprene, etc.; divinyl hydrocarbon compounds such as divinylbenzene, etc.; and alkenyl cyanides such as acrylonitrile, methacrylonitrile, etc. Among them, 1,3-butadiene and acrylonitrile are preferred. These compounds can be used alone or as a mixture of two or more.

[0061] Preferably, the functional alkenyl compound (A) is used in a proportion of less than 50% by weight relative to the weight of the monomer mixture, and the non-functional alkenyl compound (B) is used in a proportion of less than 30% by weight relative to the weight of the monomer mixture.

[0062] According to a preferred embodiment, the adhesive composition is provided in a non-crosslinked form. In alternative embodiments, the adhesive composition as described herein can be crosslinked by the self-condensation of its functional groups or by reacting with a catalyst and / or a crosslinking agent, such as melamine resins, epoxy resins, etc., and known low molecular weight crosslinking agents, such as di- or higher polyisocyanates, polyaziridines, polycarbodiimides, polyoxazolines, dialdehydes (such as glyoxal), acetoacetates, malonates, acetals, di- and tri-functional acrylates and thiols, alicyclic epoxy molecules, organosilanes (such as epoxysilanes and aminosilanes), carbamates, diamines and triamines, inorganic chelating agents (such as some zinc salts and zirconium salts), titanium, glycolurils and other amino plastics. In some cases, functional groups derived from other polymeric components (such as surfactants, initiators, seed particles) can participate in the crosslinking reaction. When two or more functional groups are involved in the crosslinking process, the complementary reactive group pairs are, for example, hydroxyl-isocyanate, acid-epoxy, amine-epoxy, hydroxyl-melamine, acetoacetate-acid. Monomers that do not contain functional groups that can enter into the crosslinking reaction after polymerization should preferably account for 70% by weight or more of the total mixture of monomers, and more preferably should be greater than 90% by weight. According to one embodiment, the adhesive composition comprises a crosslinking agent selected from isocyanates, diamines, adipic acid, dihydrazides and combinations thereof.

[0063] In the adhesive composition, the P1 / P2 mass ratio may vary from 99 / 1 to 5 / 95, preferably from 95 / 5 to 50 / 50, advantageously from 95 / 5 to 60 / 40.

[0064] In a preferred embodiment, the adhesive composition has a solution viscosity (9 wt% in NMP) of less than 15000 cP, measured at 3.36 s-1 on a Brookfield DVII viscometer with a SC24-25 spindle at 25° C. Advantageously, the adhesive composition has a 9 wt% solution viscosity in NMP of less than 14000 cP, preferably less than 13000 cP, more preferably less than 12000 cP, and in particular less than 11000 cP, measured at 3.36 s-1 on a Brookfield DVII viscometer with a SC24-25 spindle at 25° C.

[0065] In a particular embodiment, the adhesive of the invention consists of said polymer P1 and said polymer P2 as defined herein.

[0066] In a preferred embodiment, the adhesive composition of the present invention exhibits a morphology of an interpenetrating polymer network (IPN) type, wherein the chains of polymer P1 and the chains of hydrophilic polymer P2 are entangled. An interpenetrating polymer network (IPN) is a polymer comprising two or more networks, which are at least partially interwoven on a molecular scale but are not covalently bonded to each other and cannot be separated unless chemical bonds are broken. The morphology of the interpenetrating polymer network (IPN) type may also refer to a polymer comprising one or more polymer networks and one or more straight or branched polymers, characterized in that at least one of the networks is penetrated by at least some of the straight or branched macromolecules on a molecular scale. A mixture of two or more preformed polymer networks is not an IPN. In particular, the adhesive composition of the present invention exhibits a sequential interpenetrating polymer network. The latter is an interpenetrating polymer network prepared by a method wherein a second component network is formed after forming a first component network. It has been observed that, compared with a corresponding dry blend, the adhesive composition according to the present invention exhibiting this morphology has improved adhesive properties.

[0067] The interpenetrating polymer network is formed by making at least one of the formula R 1 R 2 C=C(R 3 )C(O)R(I) and optionally monomers M2 as defined above, by polymerization in the presence of said polymer P1 used as seed.

[0068] In an alternative embodiment, the adhesive composition is a dry blend of polymer P1 and a hydrophilic polymer P2 as defined in the present application.

[0069] In a second aspect of the present invention, a method for producing an adhesive composition is provided.

[0070] In a preferred embodiment, the method comprises the following steps:

[0071] a) providing an aqueous solution comprising a polymer P1 comprising repeating units derived from vinylidene fluoride;

[0072] b) adding at least one compound of formula R as defined in the present application 1 R 2 C=C(R 3 )C(O)R(I) monomer M1 and optionally one or more monomers from which the repeating units of the hydrophilic polymer P2 are derived;

[0073] c) adding an initiator and initiating polymerization of the monomer M1 and optionally one or more monomers from which the repeating units of the hydrophilic polymer P2 are derived, to prepare an adhesive composition according to the invention. This process is particularly suitable for preparing an adhesive composition according to the invention exhibiting an interpenetrating polymer network (IPN) type morphology.

[0074] In a preferred embodiment, said step b) of the process is carried out in the absence of a chain transfer agent or in the presence of less than 1.2 wt%, preferably less than 1.0 wt% of a chain transfer agent based on the total weight of all monomers added in step b).

[0075] Chain transfer agents are added to the polymerization to adjust the molecular weight of the product. They can be added to the polymerization in a single portion at the beginning of the reaction, or added to the polymerization incrementally or continuously throughout the reaction. The amount and mode of addition of the chain transfer agent depend on the activity of the specific chain transfer agent used and the desired molecular weight of the polymer product. Oxidized compounds such as alcohols, carbonates, ketones, esters and ethers can be used as chain transfer agents. Examples of oxidized compounds that can be used as chain transfer agents include isopropanol, as described in U.S. Patent No. 4,360,652. Other classes of compounds that can be used as chain transfer agents in the polymerization of halogen-containing monomers include, for example, halogenated hydrocarbons and hydrohalogenated hydrocarbons, such as chlorohydrocarbons, or mercaptans, such as n-dodecyl mercaptan or 3-mercaptopropionic acid isooctyl ester. Alkanes such as ethane and propane can also be used as chain transfer agents. Chain transfer agents can be added to steps b) and / or c) of the inventive method.

[0076] The term initiator refers to a chemical that can provide a free radical source, which is induced spontaneously or by exposure to heat or light. Examples of suitable initiators include peroxides, peroxydicarbonates and azo compounds. "Initiator" also includes a redox system that can be used to provide a free radical source. The term "radical" and the expression "free radical" refer to a chemical substance containing at least one unpaired electron. The free radical initiator is added to the reaction mixture in an amount sufficient to initiate the polymerization reaction and maintain the polymerization reaction at a desired reaction rate. The order of addition can vary according to the desired method and latex emulsion properties. The free radical initiator can include persulfates, such as sodium persulfate, potassium persulfate or ammonium persulfate. The amount of persulfate added to the reaction mixture (based on the total weight of the monomer added to the reaction mixture) can be, for example, about 0.002 to about 1.0 weight %. The free radical initiator can include an organic peroxide, such as an alkyl, dialkyl or diacyl peroxide, peroxydicarbonate and peroxyester or a mixture thereof. A preferred alkyl peroxide is tert-butyl hydroperoxide. Preferred dialkyl peroxides are di-tert-butyl peroxide (DTBP). Organic peroxides can be added to the reaction mixture in an amount of about 0.01 to about 5% by weight of the total monomers, and are preferably added in an amount of about 0.05 to about 2.5% by weight of the total monomers. Preferred peroxydicarbonate initiators are di-n-propyl peroxydicarbonate and diisopropyl peroxydicarbonate, which can be added to the reaction mixture in an amount of about 0.5 to about 2.5% by weight of the total monomers. Peroxyester initiators include tert-amyl peroxypivalate, tert-butyl peroxypivalate and succinic acid peroxide. Free radical initiators may include azo initiators, such as 2,2'-azobis(2-methylpropionamidine)dihydrochloride. Free radical initiators may include a redox system. "Redox system" refers to a system comprising an oxidant, a reductant and optionally a promoter as an electron transfer medium. Oxidants include, for example, persulfates; peroxides such as hydrogen peroxide; hydroperoxides such as tert-butyl hydroperoxide and cumene hydroperoxide; and oxidized metal salts such as ferric sulfate. Reducing agents include, for example, sodium formaldehyde sulfoxylate, sodium sulfite and potassium sulfite, ascorbic acid, bisulfite, metabisulfite and reduced metal salts. Promoters are components of redox systems that can react with both oxidants and reductants in different oxidation states to accelerate the overall reaction. Promoters include, for example, transition metal salts such as ferrous sulfate. In a redox system, oxidants and reductants can be used in an amount of about 0.01 to about 0.5% by weight based on the total monomers. Optional promoters can be used in an amount of about 0.005 to about 0.025% by weight based on the total monomers.Redox systems are described in GSMisra and UDN Bajpai, Prog. Polym. Sci., 1982, 8(1-2), pp. 61-131.

[0077] The process can also be carried out in the presence of surfactants, in particular non-fluorinated surfactants. Among the non-fluorinated surfactants, mention may be made of nonionic emulsifiers, such as notably alkoxylated alcohols, for example ethoxylated alcohols, propoxylated alcohols, mixed ethoxylated / propoxylated alcohols; anionic surfactants, notably including fatty acid salts, alkyl sulfonates (e.g. sodium lauryl sulfate), alkyl aryl sulfonates, aryl alkyl sulfonates, etc.; organic modified siloxanes, for example siloxanes modified with polyethers, primary hydroxyl groups or side chains with double bonds.

[0078] The binder composition obtained by the inventive method is preferably in the form of latex, which is defined as a colloidal dispersion of a polymer dispersed in a continuous (usually aqueous) phase. The polymerized product is preferably a latex, which can be used in this form (usually after filtering out the solid byproducts of the polymerization process). In order to use it in the form of latex, the latex can be stabilized by adding a surfactant (surface-active agent), which can be the same or different (if appropriate) from the surfactant present during the polymerization. This surfactant added later can be, for example, an ionic or nonionic surfactant.

[0079] The adhesive composition may alternatively be recovered as a powder for redistribution into water or an organic solvent.Thus, the process may further comprise the step of drying the adhesive composition obtained in step c) of the process.

[0080] Therefore, the adhesive composition of the present invention is preferably a latex or a powder.

[0081] The binder composition according to the present invention is a part of an electrode composition, in particular a positive electrode composition.

[0082] In another aspect of the present invention, an electrode composition, in particular a positive electrode composition, is provided, which comprises the binder composition according to the present invention, a conductive agent and an active material.

[0083] The conductive agent is preferably selected from carbon black such as acetylene black, Ketjen black; carbon fibers such as carbon nanotubes, carbon nanofibers, vapor-grown carbon fibers; metal powders such as SUS powders and aluminum powders; or mixtures thereof.

[0084] The active material is preferably selected from lithium salts of transition metal oxides, sulfides, phosphates and hydroxides. Preferably, the active material is selected from lithium metal phosphates (having a composition represented by LiMPO4, M represents Fe, Mn, Co, or Ni), LiCoO2, LiNi x Co 1-x O2, LiMn2O2, LiNiO2, LiNi x Co y Mn z O m 、LiNi x Co y Al z O m and LiNi x Mn y Al z O m , where x+y+z=1, and m is an integer representing the number of oxygen atoms in the oxide to provide electron balance molecules.

[0085] More preferably, the active material is selected from LiFePO4 and LiNi x Co y Mn z O m , wherein x is greater than or equal to 0.6, y is less than or equal to 0.2, z is greater than or equal to 0.2, and x+y+z=1, and m is an integer representing the number of oxygen atoms in the oxide to provide electron balance molecules.

[0086] In particular, the active material is selected from LiFePO4 and LiNi x Co y Mn z O m , wherein x is greater than or equal to 0.8, y is less than or equal to 0.1, z is greater than or equal to 0.1, and x+y+z=1, and m is an integer representing the number of oxygen atoms in the oxide to provide electron-balanced molecules.

[0087] The electrode composition may further comprise a solvent, such as water or an organic solvent.

[0088] The organic solvent is preferably selected from N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), triethyl phosphite (TEP), acetone, cyclopentanone, tetrahydrofuran, methyl ethyl ketone (MEK), methyl isobutyl ketone (MiBK), ethyl acetate (EA), butyl acetate (BA), ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), γ-butyrolactone and N-butylpyrrolidone; and combinations thereof.

[0089] The electrode composition is generally prepared by mixing the components, ie, the binder composition, the active material, the conductive agent and optionally a solvent. When the components are mixed in the presence of an organic solvent, the binder is preferably in the form of a powder.

[0090] In another aspect of the present invention, a positive electrode is provided. The positive electrode includes a current collector and the electrode composition according to the present invention disposed on at least one surface of the current collector. Once the electrode composition is disposed on at least one surface of the current collector, the electrode is dried to remove the organic solvent or water.

[0091] According to a preferred embodiment, after evaporation of the organic solvent or water, the electrode composition cast on the current collector has the following mass composition:

[0092] a. 80% to 99.9% active substance, preferably 80% to 99%,

[0093] b. 0.05% to 10% of a conductive agent, preferably 10% to 0.5%,

[0094] c. 0.05% to 10% of the adhesive composition of the present invention, preferably 10% to 0.5%; the sum of all these percentages is 100%.

[0095] The present invention also provides a Li ion secondary battery. The Li ion secondary battery comprises a negative electrode, a positive electrode according to the present invention, and a separator between the negative electrode and the positive electrode.

[0096] In another aspect of the present invention, an electrochemical device is provided, wherein the electrochemical device comprises a negative electrode, a positive electrode according to the present invention, and an electrolyte containing lithium.

[0097] Example

[0098] The following examples illustrate the scope of the present invention without limiting the scope of the invention.

[0099] Preparation of Adhesive Compositions (Adhesives 1 to 4 Exhibiting IPN-Type Morphology)

[0100] Use polyvinylidene fluoride latex as the seed of synthetic adhesive composition, wherein PVDF and hydrophilic polymer form interpenetrating network. 1000g PVDF latex and 500g deionized water are added to 2 liter reactor. 32g acrylic monomer mixture (corresponding to the repeating unit of hydrophilic polymer P2), 3.2g 10.0 wt% VAZO-67 solution in tripropylene glycol methyl ether and optional chain transfer agent (such as 3-mercaptopropionic acid isooctyl ester) are added to the reactor. The reactor temperature is increased between 50 ℃ and 100 ℃. 11.0g 3.5% tert-butyl hydroperoxide is fed into the reactor. Stir the mixture and cool to room temperature. The adhesive composition is discharged from the reactor. The product can be spray dried into powder or used as latex. All embodiments are prepared according to the above procedure. The amount of PVDF latex, hydrophilic monomer and chain transfer agent used in each example is listed in Table 1 below.

[0101] Preparation of Adhesive Composition (Adhesive 5 - Dry Blend)

[0102] An adhesive composition based on a dry blend of PVDF and a hydrophilic polymer was also prepared. This adhesive composition was prepared by dry blending the PVDF used as seed for preparing Adhesive 2 and a hydrophilic polymer P2 obtained according to the same procedure detailed above except that no PVDF seed was used.

[0103] Determination of Mw of hydrophilic polymer P2

[0104] The weight average molecular weight of the hydrophilic polymer P2 was determined by preparing the hydrophilic polymer according to the same procedure as detailed above, except that no polyvinylidene fluoride seed was used, and the hydrophilic polymer thus obtained was collected and analyzed by GPC. The GPC analysis was performed on a Waters 2695e coupled to a Wyatt Wyatt NEON refractometer equipped with two PL gel mixed C columns and a guard column (7.8 mm ID×30 cm, 5 μm) under the following conditions:

[0105] - Temperature: 35°C;

[0106] - Flow rate: 1.0 mL / min;

[0107] - Injection volume: 100 μL.

[0108] The samples were provided as solids and prepared at 1 mg / mL (HPLC grade) in THF. Calibration was performed using twelve poly(methyl methacrylate) standards with Mp ranging from 535 to 2,210,000 g / mol. The calibration data were fitted to R 2 is a cubic polynomial of at least 0.999.

[0109] [Table 1]

[0110]

[0111]

[0112] 1 % based on the amount of methyl methacrylate (MMA) and methacrylic acid (MAA); 2 PVDF homopolymer *Mw of hydrophilic polymer P2 (copolymer of MMA and MAA); **9% in NMP measured at 25°C on a Brookfield DVII viscometer with a SC4-25 spindle at 3.36 s-1

[0113] Preparation of electrode compositions

[0114] NMC as active material

[0115] The electrode composition for the cathode was prepared by a wet mixing method. A binder solution (4.66 g of a 9% solution in NMP) was prepared by dissolving the binder composition in NMP. The active material (carbon black - 0.42 g), mixed, and then diluted with NMP. A wet mixed formulation was prepared using a Thinky ARE-310 mixer. Carbon black was added to a Thinky cup and then the binder composition in the NMP solution was added. The mixture was mixed at 2000 rpm. The active material (NMC 811 - 27.16 g) was added together with NMP. The total amount of NMP was (3.36 mL). The resulting electrode composition was cast onto aluminum foil using a spatula. The electrode was dried in an oven at 120 ° C to evaporate the NMP. The electrode was rolled and then tested for physical properties. Adhesion was measured in a 180 ° peel test according to ASTM D903. The results are reported in Table 2.

[0116] [Table 2]

[0117] Example CTA % Peeling (N / m) Adhesive 1 0 133 Adhesive 2 0.3 142 Adhesive 3 0.6 141 Adhesive 4 1.2 118 Adhesive 5 0.6 125 Adhesive 6 (Comparative) 0 58

[0118] As the results detailed in Table 2 clearly demonstrate, the adhesive composition according to the present invention provides enhanced properties compared to an adhesive composition consisting of PVDF alone (Adhesive 6). When the adhesive composition exhibits an IPN morphology, the peel adhesion is further improved compared to the dry blend.

[0119] LiFePO4 as active material

[0120] Peel Adhesion

[0121] The peel adhesion of electrode compositions containing LiFePO4 as an active material instead of NMC 811 was also evaluated. For all formulations, the electrode compositions were made of Lenergy N2 lithium iron phosphate (LiFePO4 or LFP) as a cathode active material and carbon black (Super PC65) as a conductive agent. The weight ratio of active material / conductive agent / binder was 94 / 3 / 3. All procedures were carried out in a dry room environment (temperature = 20°C, dew point = -50 to -60°C). The electrode composition was cast on aluminum foil with an adjustable 150mm wide film applicator (scraper, Elcometer3580 / 5) to prepare the electrode. All electrodes were dried in a convection oven at 120°C for at least 30 minutes, and each electrode was cut into three 1-inch wide strips for peel adhesion measurement. Each electrode strip was calendered at 0.1MPa with an HSTK-1515H roller press to achieve 10.5 to 11.5mg / cm 2 Mass loading and 2~2.1g / cm 3 Electrode density. For the peeling evaluation of each formulation, three electrode strips cut from the same electrode sheet were conditioned in a drying chamber for three days, and then the 180° peeling adhesion was measured using an Instron 3340 load frame with a 10N load cell (method based on ASTM D903). The values ​​were averaged to determine the peeling adhesion of each adhesive sample.

[0122] The results are detailed in Table 3 below.

[0123] [Table 3]

[0124] Example P1 / P2 mass ratio Peel Adhesion(N / m) Adhesive 2 90 / 10 56.7 Adhesive 3 90 / 10 53.9 Adhesive 4 90 / 10 52.2 Adhesive 6 (Comparative) 100 / 0 30.3

[0125] As the results of Table 3 clearly demonstrate, the electrode compositions prepared with the binder according to the present invention have improved peel adhesion compared to PVDF alone.

[0126] Slurry stability

[0127] The slurry stability was also evaluated by using a Brookfield cone and plate LVDV-III Ultra viscometer with a rotational method to change the shear rate between 0.1 and 20s-1 while recording the viscosity. The initial slurry viscosity (0d viscosity) was measured on the same day of the formulation. The slurry was mixed at 2000rpm in Thinky for 30 seconds and then sampled. The slurry samples were then placed in the same tightly closed Thinky jar in a drying room until the time for the 3-day viscosity measurement. All viscosity measurements were performed in a non-drying room laboratory fume hood. The results are detailed in Table 4 below.

[0128] [Table 4]

[0129]

[0130] Compared to PVDF alone (Binder 6 - Comparative), the adhesive composition according to the invention showed better stability over time.

Claims

1. A binder composition for a positive electrode, comprising a polymer P1 and a hydrophilic polymer P2, wherein the polymer P1 comprises a repeating unit derived from vinylidene fluoride, and the hydrophilic polymer P2 comprises at least a repeating unit derived from a compound of formula R 1 R 2 C=C(R 3 )C(O)R(I) is a repeating unit of at least one monomer M1, wherein R 1 , R 2 and R 3 R is selected from -NHC(CH3)2CH2C(O)CH3, -NR'R" or -OR', wherein R' and R" are independently selected from H and C1-C5 alkyl; 18 an alkyl group, which is optionally substituted with one or more hydroxyl, thiol or amino functional groups or a five- to six-membered heterocyclic ring containing at least one nitrogen atom in the ring; Features The weight average molecular weight of the hydrophilic polymer P2 is greater than 30,000 g / mol, advantageously greater than 50,000 g / mol, preferably greater than 65,000 g / mol, more preferably greater than 80,000 g / mol.

2. Adhesive composition according to the preceding claim, wherein said polymer P1 and said hydrophilic polymer P2 form an interpenetrating polymer network.

3. Adhesive composition according to the preceding claim, wherein said interpenetrating polymer network is obtained by polymerization of formula R in the presence of said polymer P1 used as seed 1 R 2 C=C(R 3 )C(O)R(I) is obtained by at least one of the monomers M1. 4 . The adhesive composition according to claim 1 , wherein the polymer P1 is chosen from polyvinylidene fluoride homopolymers and polyvinylidene fluoride-based copolymers comprising at least one comonomer compatible with vinylidene fluoride.

5. Adhesive composition according to the preceding claim, wherein the comonomer is selected from vinyl fluoride, tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, chlorotrifluoroethylene, trifluoropropylene, tetrafluoropropylene, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene, perfluoroalkyl vinyl ether, bromotrifluoroethylene, chlorofluoroethylene, chlorotrifluoroethylene, chlorotrifluoropropylene and ethylene, or mixtures thereof.

6. Adhesive composition according to any of the preceding claims, wherein the polymer P1 comprises monomer units carrying at least one of the following functional groups: carboxylic acid, carboxylic anhydride, carboxylic ester, epoxy, amide, hydroxyl, carbonyl, mercapto, sulfide, oxazoline, phenol, ester, ether, siloxane, sulfonic acid, sulfuric acid, phosphoric acid or phosphonic acid.

7. An adhesive composition according to any one of the preceding claims, wherein the hydrophilic polymer P2 comprises at least repeating units derived from at least one monomer M1 selected from the group consisting of acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-dodecyl acrylate, amyl acrylate, isoamyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, diacetone acrylamide, lauryl acrylate, n-octyl acrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-dodecyl methacrylate, amyl methacrylate, isoamyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, n-octyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl methacrylate, and combinations thereof.

8. Adhesive composition according to any of the preceding claims, wherein the mass ratio P1 / P2 varies between 99 / 1 and 5 / 95.

9. Adhesive composition according to any one of the preceding claims, wherein the polymer P1 has a melt viscosity measured according to ASTM D-3835 method at 232°C and 100 sec-1 of greater than 100 Pa.s, preferably greater than 500 Pa.s, more preferably greater than 1000 Pa.s.

10. A method for producing an adhesive composition comprising the steps of: a) providing an aqueous solution comprising a polymer P1 comprising repeating units derived from vinylidene fluoride; b) adding a compound of formula R as defined in any one of the preceding claims 1 R 2 C=C(R 3 ) at least one monomer M1 of C(O)R(I) and optionally one or more monomers from which the repeating units of the hydrophilic polymer P2 are derived; c) adding an initiator and initiating polymerization of the monomer M1 and optionally one or more monomers from which the repeating units of the hydrophilic polymer P2 are derived, to produce an adhesive composition according to any one of the preceding claims.

11. Process according to the preceding claim, wherein step b) is carried out in the absence of a chain transfer agent or in the presence of less than 1.2 wt. %, preferably less than 1.0 wt. %, of a chain transfer agent, based on the total weight of all monomers added in step b).

12. An electrode composition comprising the binder composition according to any one of the preceding claims, a conductive agent and an active material.

13. Electrode composition according to the preceding claim, wherein the conductive agent comprises one or more materials selected from carbon black, carbon nanotubes, carbon fibers or metal powders.

14. An electrode composition according to any one of the preceding claims 11 to 12, wherein the active material is selected from lithium salts of transition metal oxides, sulfides, phosphates and hydroxides; preferably, the active material is selected from lithium metal phosphates having a composition represented by LiMPO4, M represents Fe, Mn, Co, or Ni; LiCoO2; LiNi x Co 1-x O2; LiMn2O2; LiNiO2; LiNi x Co y Mn z O m ,LiNi x Co y Al z O m , and LiNi x Mn y Al z O m , wherein x+y+z=1, and m is an integer representing the number of oxygen atoms in the oxide to provide electron balance molecules; in particular, the active material is selected from LiFePO4 and LiNi x Co y Mn z O m , wherein x is greater than or equal to 0.6, y is less than or equal to 0.2, z is greater than or equal to 0.2, and x+y+z=1, and m is an integer representing the number of oxygen atoms in the oxide to provide electron balance molecules.

15. A positive electrode comprising a current collector and the electrode composition according to any one of the preceding claims 11 to 13 disposed on at least one surface of the current collector.

16. A Li-ion secondary battery comprising a negative electrode, a positive electrode according to claim 14, and a separator between the negative electrode and the positive electrode.

17. An electrochemical device comprising a negative electrode, a positive electrode according to claim 14, and an electrolyte containing lithium.

Citation Information

Patent Citations

  • Slurry for lithium ion secondary battery positive electrodes

    EP2953193A1

  • Electrode mixture, electrode mixture production method, electrode structure, electrode structure production method, and secondary battery

    EP3796430A1

  • Electrode, nonaqueous electrolyte battery, and battery pack

    US20130252077A1

  • Fluoropolymer dispersion for separator coating

    US20200407543A1

  • Method of preparing high quality vinylidene fluoride polymer in aqueous emulsion

    US4360652A

Cited By

  • Modified polyvinylidene fluoride binder as well as preparation method and application thereof

    CN121249292A

  • A modified polyvinylidene fluoride binder, its preparation method and application

    CN121249292B